Microstructure and Mechanical Properties of Copper–steel Laminated and Sandwich Joints Prepared by Electron Beam Welding - Debin, Song; Ting, Wang; Siyuan, Jiang; Liang, Zhang (Journal of materials engineering and performance, 2020)
Laminated and sandwich joints composed of copper and 304 stainless steel with different stacking sequences were prepared by electron beam welding. The analysis of microstructures, element distribution and mechanical properties of the joints were carried out. Joints under all parameters were well formed without defects such as pores and cracks. The microstructures of the welds were mainly composed of (Cu, Fe) solid solution [(Cu, Fe)ss]. It was also found that the shear strength of the joint and the content of α-phase at the interface had a linear relationship. For laminated joints, the shear strength of steel/copper joint was increased by 12.7% compared with copper/steel joint, and the shear strength value reached 420 MPa. The scanning electron beam could refine microstructures and increase the weld width and improve the mechanical properties of the joints significantly. The tensile strength of the sandwich joint with steel as the intermediate layer was increased by 17.4% compared with the joint with copper as the intermediate layer.